2009
DOI: 10.1021/la903806a
|View full text |Cite
|
Sign up to set email alerts
|

Novel Type of Bicellar Disks from a Mixture of DMPC and DMPE-DTPA with Complexed Lanthanides

Abstract: We report on the formation of bicelles from a mixture of dimyristoylphosphatidylcholine (DMPC) and the chelator-lipid dimyristoylphosphatidylethanolamine-diethylenetriaminepentaacetate (DMPE-DTPA) with complexed lanthanides, either thulium (Tm(3+)) or lanthanum (La(3+)). The two phospholipids used have the same acyl-chain length but differ in headgroup size and chemical structure. The total lipid concentration was 15 mM, and the molar ratio of DMPC to DMPE-DTPA was 4:1. The system was studied with small angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 40 publications
4
60
0
Order By: Relevance
“…Upon tilting the sample holder by 20°, a circular feature became rod-shaped, revealing the discoid structure of the nanodiscs (Figure 3B). 29,30 Results obtained from dynamic light scattering (DLS) experiments confirmed that the addition of a polymer to DMPC vesicles resulted in a significant decrease in the hydrodynamic diameter ( D hy ) and the formation of the monodispersed assembly in water (Figure 4A), reflecting that the vesicles in the solution were completely solubilized by the polymer to form lipid nanodiscs. Additionally, the hydrodynamic diameter of the polymer–lipid assembly was systematically examined by changing the lipid:polymer molar ratio (Figure 4B).…”
Section: Resultsmentioning
confidence: 89%
“…Upon tilting the sample holder by 20°, a circular feature became rod-shaped, revealing the discoid structure of the nanodiscs (Figure 3B). 29,30 Results obtained from dynamic light scattering (DLS) experiments confirmed that the addition of a polymer to DMPC vesicles resulted in a significant decrease in the hydrodynamic diameter ( D hy ) and the formation of the monodispersed assembly in water (Figure 4A), reflecting that the vesicles in the solution were completely solubilized by the polymer to form lipid nanodiscs. Additionally, the hydrodynamic diameter of the polymer–lipid assembly was systematically examined by changing the lipid:polymer molar ratio (Figure 4B).…”
Section: Resultsmentioning
confidence: 89%
“…In a similar approach, the lipid dimyristoylphosphatidylethanolamine (DMPE) extended by a diethylenetriaminepentaacetate (DTPA) group chelating a paramagnetic Tm 3+ or La 3+ lanthanide ion was used instead of PEGylated lipids. Formation of flat discoidal aggregates was observed, which in the case of Tm 3+ -doping were slightly orientable in a field of 8 T [58]. The presence of 16 mol% cholesterol in discoidal aggregates of DMPC, DMPE-DTPA, and Tm 3+ increases the disk size and the propensity for magnetic-alignment [318].…”
Section: Different Types Of Model Membranes Used In Nmr Studiesmentioning
confidence: 99%
“…Despite these attractive features, there are several reasons why conventional bicelles cannot be used as carriers for drug delivery (Figure C). Firstly, the phospholipid components of conventional bicelles have bilayer melting points ( T m ) lower than room temperature: 1,2‐dimyristoyl‐ sn ‐glycero‐3‐phosphatidylcholine (DMPC), for example, has a T m of 24 °C (Figure A). Consequently, the resulting bicelles lack kinetic stability and size tunability, because they exist in equilibrium states of rapid fusion and fission.…”
Section: Figurementioning
confidence: 99%